1981
DOI: 10.1007/bf00432438
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus control and the effects of d-amphetamine in the rat

Abstract: External discriminative stimuli can modify the behavioral effects of d-amphetamine. Previous work with the pigeon has demonstrated that some aspects of performance on the fixed consecutive number schedule are changed less if a discriminative stimulus indicates when reinforcement is available. This effect has now been replicated with the rat using both simple and multiple schedules. Moderate doses of d-amphetamine (0.56--1.0 mg/kg) usually produced large decreases in reinforced runs when no external cue indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
32
1

Year Published

1984
1984
1990
1990

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 11 publications
6
32
1
Order By: Relevance
“…As external stimulus control increases, the effects of a given dose of drug have been shown to decrease (Laties, 1972;Laties, Wood, & Rees, 1981;Thompson, 1978). The reinforcing stimuli in the present concurrent condition are also discriminative stimuli (Michael, 1982;Schuster & Balster, 1977) Although no simple and direct extrapolations can be made from these data to human situations, there is a suggestion that ethanol intakes might not be reduced at times of added ingestion of benzodiazepines if the co-use occurred in environmental situations in which other reinforcers were concurrently available.…”
Section: Discussionmentioning
confidence: 99%
“…As external stimulus control increases, the effects of a given dose of drug have been shown to decrease (Laties, 1972;Laties, Wood, & Rees, 1981;Thompson, 1978). The reinforcing stimuli in the present concurrent condition are also discriminative stimuli (Michael, 1982;Schuster & Balster, 1977) Although no simple and direct extrapolations can be made from these data to human situations, there is a suggestion that ethanol intakes might not be reduced at times of added ingestion of benzodiazepines if the co-use occurred in environmental situations in which other reinforcers were concurrently available.…”
Section: Discussionmentioning
confidence: 99%
“…Evenden and Robbins (1983b) also demonstrated that this effect of the drug did not depend upon switching being necessary for obtaining reinforcement by using concurrent random ratio schedules in which the probability of a response being reinforced was independent of switching. Furthermore, under a schedule in which subjects were required to perform a fixed consecutive number of responses in one location before switching to a second (FCN), Laties found increased switching in pigeons (Laties 1972) and rats (Laties et al 1981) under d-amphetamine, scopolamine and chlorpromazine. Moerschbaecher et al (1979) found that both amphetamine and scopolamine also increased switching in monkeys.…”
mentioning
confidence: 98%
“…In many cases, for example, the effects of drugs depend on the local rate of responding under control conditions (Dews 1958;Kelleher and Morse 1968;McKearney and Barrett 1978). In other cases, reinforced behavior under strong control of a discriminative stimulus is affected by drugs differently than behavior controlled exclusively by schedule presentations of the reinforcer in the absence of specific enviornmental stimuli (Dews 1964;McKearney 1970;Laties and Weiss 1966;Clody and Carlton 1980;Laties et al 1981). Further, the effects of drugs on low rates of responding can depend on whether or not the low rates have resulted form suppression by punishment (Geller and Seifter 1960;Hanson et al 1967;McMillan 1973).…”
mentioning
confidence: 99%